2020
DOI: 10.1124/dmd.120.000050
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Traditional Chinese Medicine on P-Glycoprotein–Mediated Multidrug Resistance and Approaches for Studying the Herb–P-Glycoprotein Interactions

Abstract: As a member of the ATP-dependent membrane transport proteins, P-Glycoprotein (P-gp) is known to pump substrates out of cells using an ATP-dependent mechanism. The overexpression of P-gp in tumor cells reduces the intracellular drug concentrations, which decreases the efficacy of extensive antitumor drugs and leads to multidrug resistance (MDR) clinically. The combination of anticancer drugs with P-gp inhibitor has been an attractive and promising strategy to reverse MDR in cancer treatment. However, nonspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…P-glycoprotein (P-gp) inhibitors, RNA interference, nano drugs, and combination drugs are new strategies against MDR; however, current clinical trials of related transporter protein inhibitors have been unsuccessful and have shown toxic side effects of these drugs ( Mohammad et al., 2020 ; Robey et al., 2018 ; Tian et al., 2012 ). Baicalein is a substrate of P-gp and competitively inhibits P-gp to enhance anticancer activity, and flavonoids and alkaloids also modulate P-gp, the main active component of GQD ( Cao et al., 2020 ; Palko-Labuz et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein (P-gp) inhibitors, RNA interference, nano drugs, and combination drugs are new strategies against MDR; however, current clinical trials of related transporter protein inhibitors have been unsuccessful and have shown toxic side effects of these drugs ( Mohammad et al., 2020 ; Robey et al., 2018 ; Tian et al., 2012 ). Baicalein is a substrate of P-gp and competitively inhibits P-gp to enhance anticancer activity, and flavonoids and alkaloids also modulate P-gp, the main active component of GQD ( Cao et al., 2020 ; Palko-Labuz et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…More and more attention has been paid to the development of new inhibitors from natural products of traditional Chinese medicine (TCM). Some TCM extracts, such as flavonoids, alkaloids, terpenoids, coumarins, and quinones, have been reported to have a good ability of inhibiting P‐gp and reversing MDR [94] …”
Section: Strategies To Reduce Efflux Protein Expressionmentioning
confidence: 99%
“…In fact, over 90% of chemotherapy failures amidst patients with malignant tumors are related to MDR, resulting in unfavorable prognosis, recrudescent disease, and a decreased subsistence rate [5,6]. Recently, combination therapy of chemo-drugs with P-glycoprotein (P-gp)-targeted small-molecule inhibitors has been considered an advantageous approach in MDR reversal as numerous anticancer agents belong to substrates of P-gp, which is an overexpressed drug-efflux transporter, especially in malignant cells [7]. Unfortunately, although the present three generations of P-gp suppressants, including verapamil, biricodar, and elacridar, can restore the efficacy of chemotherapeutic drugs in vitro and in vivo, they seldom have been approved for clinical use due to some deficiencies, such as improper interactions with therapeutic agents and intolerable systemic adverse effects [8][9][10].…”
Section: Introductionmentioning
confidence: 99%